Adoption of improved varieties in adverse climatic conditions: Evidence from Nicaragua - Reyes, Byron A.; Ibarra Medina, Lina Marcela; Gomez, Lorena; Labarta, Ricardo Antonio (2022)
This presentation summarizes the main results of a study made in Nicaragua to estimate the adoption of improved bean varieties (IVs) across different climatic environments, and the yield differences between adopters and non-adopters. We implemented a farmer-level survey representative of the most productive bean regions in the country. The results show that when comparing dry vs. non-dry regions ("corridors"), yields are 10.9% lower in the dry region; 29-31% of farmers have adopted IVs in non-dry and dry regions, respectively; and 28-29% of the bean area was planted to IVs in non-dry and dry regions, respectively. Although IV yields are statistically the same to non-IV yields (farmer-reported use of IVs), in dry regions, improved bean varieties yield 14.7% more than non-IVs, which is enough to feed 6-7 people for a year. This yield advantage (of IVs) dissapears under extreme dry conditions.